Euphemism: The commonplace of advertising culture - Taofeek Olaiwola Dalamu (Acta Scientiarum. Language and Culture, 2018)
Politeness is a concern and necessity in advertising because of sensitization goals to be achieved in the midst of cultural, legal and competitive challenges. Thus, this study examined the utilization of euphemistic devices that facilitate mild persuasion in advertisements. Ten advertisements served as the data of investigation. The theoretical explication rested on Barthesian denotative and connotative annotations and Halliday’s transitivity concepts. The study revealed concealments in forms of the socio-cultural affiliation and association (solo), domination (power, the Hero), distinction (made of more), and superiority (Indomitables). Also, personification and personalization (bigger boy; your world), self-worth (greatness), borrowing (Naija), and transfer of professional meaning (credit card) functioned as replacements for seemingly inappropriate lexicons. Advertisers hide behind the metaphor (a taste of black), discrimination (choose greatness), and comparison (more, bigger) to expedite recipients’ response. Therefore, as euphemisms are everyone’s linguistic behavior, the study suggested that their analyses and applications need to follow a similar course. That might assist language users to curb communication crises.